FRI0411 Coadministration of bosentan has no effect on the pharmacokinetics of nintedanib. (15th June 2017) - Wind, S; Simons, G; Bertulis, J; Coeck, C
Abstract : Background: Nintedanib is a potent intracellular inhibitor of tyrosine kinases that has been approved for the treatment of idiopathic pulmonary fibrosis and is being investigated as a treatment for interstitial lung disease associated with systemic sclerosis (SSc-ILD). Bosentan is a dual endothelin receptor antagonist used in the treatment of pulmonary arterial hypertension, which is a common comorbidity of SSc-ILD. Objectives: To ascertain the effect of bosentan on the pharmacokinetics of nintedanib. Methods: In an open-label, single-centre study, healthy male subjects aged ≥18 and ≤55 years with a body mass index (BMI) ≥18.5 and ≤29.9 kg/m 2 received a single dose of nintedanib 150 mg alone (period 1) followed by bosentan 125 mg twice daily (bid) for 8 days (bosentan loading dose phase on days 1–6) with a single dose of nintedanib 150 mg on day 7 (period 2). The primary endpoints were the maximum plasma concentration (Cmax ) of nintedanib and the area under the plasma concentration-time curve from time 0 to the last quantifiable concentration (AUC0-tz ) of nintedanib. The secondary endpoint was the AUC from time 0 extrapolated to infinity (AUC0–∞ ) for nintedanib. Results: Thirteen subjects (12 White; mean [SD] age 35.0 [9.8] years and BMI 24.5 [2.5] kg/m 2 ) were treated. All subjects completed the planned observation period. Based on Cmax, AUC0-tz and AUC0–∞, exposure to nintedanib was similar after a single dose of nintedanib given alone or in combination with multiple doses of bosentan 125 mg bid (Table). Adverse events were reported in 4 subjects (30.8%) on nintedanib alone (period 1), 4 subjects (30.8%) on bosentan 125 mg bid (days 1–6 of period 2) and 2 subjects (15.4%) after administration of bosentan with nintedanib (days 7 and 8 of period 2). All adverse events were mild in intensity. Conclusions: Coadministration of bosentan 125 mg bid had no effect on the pharmacokinetics of a single dose of nintedanib 150 mg. Disclosure of Interest: S. Wind Employee of: Boehringer Ingelheim Pharma GmbH & Co. KG, G. Simons Employee of: Boehringer Ingelheim Pharma GmbH & Co. KG, J. Bertulis Employee of: Boehringer Ingelheim Pharma GmbH & Co. KG, C. Coeck Employee of: Boehringer Ingelheim Pharma GmbH & Co. KG